QARAQALPAQ XALÍQ JUMBAQLARÍNDA QOLLANÍLǴAN FRAZEOLOGIZMLER - Abishov, G.M.; Sarsenbaeva, B.S. (SCIENCE and SOCIETY, 2024)
This article discusses riddles, which are one of the Karakalpak oral folk works. It reveals the importance of phraseological units in the description of the hidden word. The property of phraseological units in representing words in a figurative meaning is shown. The use of reverse arrangement of components was analyzed in the example of Karakalpak riddles.